Le corps humain à la lumière du corps du Christ ressuscité chez Thomas d’Aquin - Vetö, Étienne (Revue des sciences philosophiques et théologiques, 2016)
For Thomas Aquinas, Christ’s glorious body expresses the ultimate destiny and profound truth of the human body. The present article aims to evaluate whether this starting point allows for a real valorization of the body. In this sense, Aquinas considers the resurrected body as the completion of the logic of hylemorphism, which tends to a perfect union of body and soul, endowed with great beauty, as a « communicative » body whose senses are developed to the maximum of their acuity. The nobility of the earthly body is thus undoubtedly heightened as it prefigures and inaugurates all of this. However, the same hylemorphism implies that the glorious fate of the body occurs through its « spiritualization », its submission to the spirit to which it is assigned. It seems difficult not to read into this a subtle resistance to corporeality in it fleshy nature as well as to the tragic dimension of its finitude.